Associations between javelin throwing technique and upper extremity kinetics - Leigh, S.; Dapena, J.; Gross, M.; Li, L.; Myers, J.; Yu, B. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Javelin throwing requires great release speeds, necessitating javelin throwers to generate high forces. Their techniques exert significant musculoskeletal stress, which may cause injuries. The purpose of this study was to determine the associations between javelin throwing technique and upper extremity kinetics. Three-dimensional kinematic and kinetic data were reduced from video of javelin throwers competing in the USATF Championships. Correlations between elbow and shoulder kinetics and technique variables were calculated. High forces and torques were associated with the orientation of the javelin, shoulder horizontal adduction, and elbow flexion during the throw. These variables may be modified to reduce injury risk, however, they are also related to improved performance.